Marriage Preparation Courses in Indonesia: Comparative Study of Muslims and Christians - Batubara, Samin; Nasution, Khoiruddin; Nelli, Jumni; Nasution, Syamruddin; Sobhan , Sobhan; Kholidah, Kholidah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This paper aims to prove that after attending the Marriage Preparation Course, the prospective wives and husbands of the course participants feel the extraordinary benefits of attending the Marriage Preparation Course. Because the material presented is very relevant and vital as a provision in living household life. This paper reports the research results on implementing Marriage Preparation Courses among Muslims in Pekanbaru, Riau and Christians in Yogyakarta. These two objects result from selecting the best performance in carrying out the Marriage Preparation Course. This research includes qualitative research with a juridical approach and uses the theory of the legal system. The result of the study is that the implementation of a good Marriage Preparation Course can give a positive impression and knowledge to the course participants. The participants stated the importance of prospective wives and husbands taking Marriage Preparation Courses. This course assists candidates in dealing with the romance of domestic life in the future, especially if the material also provides testimonials of the couples. One problem to solve by working couples is not being able to get permission from the workplace to take courses. Hopefully, there will be a policy from the government that requires workplaces to permit workers to take courses in the future.